Enhancing the operational range of piezoelectric actuators by uniaxial compressive preloading. (21st April 2015) - Koruza, Jurij; Franzbach, Daniel J; Schader, Florian; Rojas, Virginia; Webber, Kyle G
Abstract: The influence of the uniaxial preload on the off-resonance actuation performance of piezoelectric ceramics was investigated for compressive preload values up to  −80 MPa. The study was performed on soft-type lead zirconate titanate (PZT), being the most widely used piezoelectric material. The samples were analysed using the proportional loading method, which enables the simultaneous application of electrical and mechanical loads, thereby mimicking the real operation conditions over the full stress–strain range. An increase of the blocking stress and the longitudinal piezoelectric stress coefficient was observed for all the applied preload values. The optimum properties, a blocking stress of  −56 MPa and a free strain of 0.23%, were obtained at a preload value of  −40 MPa and electric field of 2 kV mm   −  1 . This represents an increase of 16% and 20%, respectively, as compared to the values obtained at the smallest preload. In addition, the maximum work output was increased by about 28%. Finally, the results obtained at the lowest preload of  −4 MPa using the proportional loading method were compared to the operational ranges determined by other methods. The comparison revealed large discrepancies between the methods, originating from the different order of the application of electrical and mechanical fields and the inherent nonlinearity of ferroelectric materials. This discrepancy results in decreased actuator performance due to impedance mismatching, demonstrating the need for accurate determination of the actuator's operational range.